Particles for forming Pickering emulsions or like
By using the particles with hydrophobic and hydrophilicism department, the problem of low stability and lack of versatility in existing technologies in existing technologies, and a stable emulsification combination is formed without using surface active agents without using surface active agents. Best.
Patent Information
- Application Number
- CN202380046507.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-13
- Filing Date
- 2023-06-13
- Publication Date
- 2025-01-24
AI Technical Summary
The emulsified compositions formed by the particles used in the existing Pickering emulsions are low in stability and lack versatility.
The particles with hydrophobic and hydrophilicism are adopted. The hydrophobic department contains hydrophobic units and has a cationic group. Power combines a polymer, and is covered with the surface of the particles to improve emulsification.
Forming a stable emulsified composition without using surfactants improves the versatility and storage stability of the emulsified composition, and is suitable for cosmetics and pharmaceuticals that are in direct contact with the human body.
Smart Images

Figure CN119365547A_ABST
Abstract
Description
[0001] References to related applications
[0002] This patent application claims priority based on a previously filed Japanese patent application No. 2022-095286 (filing date: June 13, 2022). The entire disclosure of the prior patent application is incorporated herein by reference. Technical Field
[0003] The present invention relates to particles comprising predetermined hydrophobic monomer units and hydrophilic monomer units, and more preferably to particles for forming a Pickering emulsion. Background Art
[0004] Regarding emulsion compositions (emulsions) such as oil-in-water compositions and water-in-oil compositions, the aqueous component and the oily component are usually finely mixed and stably exist through the emulsification effect of the surfactants. Such emulsion compositions are widely used in daily necessities, personal care products, and biological application fields. However, when a large amount of surfactants are used in the emulsion composition, when it is directly applied to the skin and other human bodies, it will cause problems such as stickiness and irritation. Moreover, for surfactants that can be absorbed by the human body, many consumers are also worried about the impact on the human body. Therefore, it is expected to reduce the amount of surfactants used in the emulsion composition as much as possible.
[0005] In view of this situation, attempts have been made to use additives having an emulsifying effect other than surfactants in emulsified compositions. As one of such attempts, an emulsified composition emulsified by allowing solid particles to exist near the interface between an oil phase and an aqueous phase, namely, a Pickering emulsion, has attracted attention.
[0006] Figure 1 The figure schematically compares a surfactant-based emulsion with a Pickering emulsion. The present invention is not bound by any theory, but it is speculated that in Pickering emulsions, mineral particles and amphiphilic organic particles are usually present at the interface of aqueous or oily droplets, and the structure of the droplets is stabilized. As an example of a Pickering emulsion, for example, Patent Document 1 discloses a Pickering emulsion characterized in that a powder is adsorbed on an emulsified interface and the Pickering emulsion contains an acrylic polymer. According to the invention described in Patent Document 1, a Pickering emulsion having excellent emulsification stability can be provided.
[0007] In addition, Patent Document 2 discloses a cement composition, characterized in that it is a cement composition comprising cement, acrylic copolymer re-emulsified resin powder, an expansion material and a shrinkage reducing agent, wherein the average particle size of the primary particles of the acrylic copolymer re-emulsified resin powder is 0.2 μm or more and 0.8 μm or less, and the surface of the primary particles of the resin powder is coated with a water-soluble protective colloid of polyvinyl alcohol (PVA). The cement composition described in Patent Document 2 can be kneaded with water to obtain a mortar having excellent workability such as coating, a small amount of hardening shrinkage, and high bonding durability.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2019-202962
[0011] Patent Document 2: Japanese Patent Application Publication No. 2009-102216 Summary of the invention
[0012] Problems to be solved by the invention
[0013] However, various particles used in the formation of emulsion compositions such as Pickering emulsions in the past have insufficient emulsification due to the properties of the constituent parts of the particles and lack versatility. In particular, when the particles are not used in a relatively large amount in combination with a surfactant, the emulsion composition formed using the particles tends to become unstable. In addition, there are the following problems: the inorganic particles used in the formation of Pickering emulsions tend to have low emulsification stability, while the organic particles tend to have insufficient emulsification and low versatility due to the particularity of the monomers used.
[0014] Therefore, an object of the present invention is to provide particles which can form a stable emulsified composition without using a surfactant and have high versatility.
[0015] The inventors of the present application have conducted intensive research in view of the above-mentioned problems and have found that the above-mentioned problems can be solved by using particles having a hydrophobic part comprising a hydrophobic monomer unit and having a cationic group and a hydrophilic part comprising a predetermined hydrophilic monomer unit, thereby completing the present invention.
[0016] That is, the present invention provides the following solutions.
[0017] A first aspect of the present invention is a particle having: a hydrophobic portion comprising a hydrophobic monomer unit and having a cationic group; and a hydrophilic portion comprising at least a hydrophilic monomer unit represented by the following formula (I).
[0018] [Chemical formula 1]
[0019]
[0020] A second aspect of the present invention is the particle according to the first aspect, wherein a part or all of the surface of the hydrophobic portion is directly or indirectly covered with the hydrophilic monomer or a polymer thereof.
[0021] A third aspect of the present invention is the particle according to the first or second aspect, wherein the cationic group is derived from a cationic radical polymerization initiator.
[0022] A fourth aspect of the present invention is the particle according to any one of the first to third aspects, wherein the hydrophobic monomer unit is a monomer unit having an ethylenically unsaturated double bond.
[0023] A fifth aspect of the present invention is the particle according to the fourth aspect, wherein the monomer unit having an ethylenically unsaturated double bond is a (meth)acrylic monomer unit.
[0024] A sixth aspect of the present invention is the particle according to the fourth aspect, wherein the monomer unit having an ethylenically unsaturated double bond is a styrene-based monomer unit.
[0025] The seventh aspect of the present invention is the particle according to any one of the first to sixth aspects, wherein the cationic radical polymerization initiator is selected from 2,2'-[diazene-1,2-diylbis(propane-2,2-diyl)]bis(1,3-dimethyl-4,5-dihydro-1H-imidazol-3-ium)=bis(trifluoromethanesulfonate) salt (ADIP), 2,2'-[diazene-1,2-diylbis(propane-2,2-diyl)]bis(1,3-dimethyl-4,5-dihydro-1H-imidazol-3-ium)=bis(trifluoromethanesulfonate) salt (ADIP), ] At least one of the group consisting of bis(1,3-dimethyl-4,5-dihydro-1H-imidazol-3-ium)=dichloride (ADIP-Cl), 2,2'-azobis(2-methylpropionamidine) dihydrochloride (V-50), 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride (VA-044), and 2,2'-azobis[2-(2-imidazolin-2-yl)propane] (VA-061).
[0026] The eighth embodiment of the present invention is a particle described in any one of the above-mentioned embodiments 1 to 7, wherein the above-mentioned hydrophilic part also contains a monomer unit represented by the following formula (II), and the ratio (degree of saponification) of the number of monomer units represented by the above-mentioned formula (I) relative to the total number of monomer units represented by the above-mentioned formula (I) and the number of monomer units represented by the following formula (II) is greater than 70% and less than 99%.
[0027] [Chemical formula 2]
[0028]
[0029] The 9th embodiment of the present invention is the particles described in the above-mentioned 8th embodiment, wherein the ratio (degree of saponification) of the number of monomer units represented by the above-mentioned formula (I) relative to the total number of monomer units represented by the above-mentioned formula (I) and the number of monomer units represented by the above-mentioned formula (II) is greater than 78% and less than 90%.
[0030] A tenth aspect of the present invention is the particle according to any one of the first to ninth aspects, wherein the mass corresponding to the hydrophilic part is equal to 1 part by mass or more and 6 parts by mass or less with respect to 100 parts by mass corresponding to the hydrophobic part.
[0031] An eleventh aspect of the present invention is the particle according to any one of the first to tenth aspects, wherein the average zeta potential is +10 mV or more and +60 mV or less.
[0032] A twelfth aspect of the present invention is the particle according to any one of the first to eleventh aspects, wherein the cumulative average diameter is 100 nm to 500 nm.
[0033] The 13th aspect of the present invention is the particle according to the second aspect, wherein the hydrophobic monomer unit and the hydrophilic monomer unit are bonded to each other via a covalent bond, and a part or the whole of the surface of the hydrophobic part is directly covered with the hydrophilic monomer or a polymer thereof.
[0034] The 14th aspect of the present invention is the particle according to the second aspect, wherein the hydrophobic monomer unit and the hydrophilic monomer unit are bonded by intermolecular force, and a part or the whole of the surface of the hydrophobic part is indirectly covered with the hydrophilic monomer or a polymer thereof.
[0035] A fifteenth aspect of the present invention is the particle according to the fourteenth aspect, wherein the bonding by intermolecular force is caused by heat treatment.
[0036] A 16th aspect of the present invention is the particle according to any one of the 1st to 15th aspects, wherein the interfacial tension value (T 0.01 ), and the difference (T1) between the interfacial tension value (T2) between the aqueous dispersion containing 1% by mass of the above particles and decamethylcyclopentasiloxane. 0.01 -T1) is 10mN / m or more.
[0037] The 17th aspect of the present invention is the particle according to the 16th aspect, wherein the interfacial tension value (T 0.01 ) is less than 25mN / m.
[0038] The 18th embodiment of the present invention is a particle described in any one of the above-mentioned 1st to 17th embodiments, wherein, in terms of the relative ratio of the molecular weight of only the hydrophobic part to the molecular weight of only the hydrophilic part per unit particle, the hydrophilic part is greater than 1 and less than 6 relative to 100 of the hydrophobic part.
[0039] A 19th aspect of the present invention is the particle according to any one of the 1st to 18th aspects, wherein the residual rate of the insoluble fraction after extraction with a Soxhlet extractor using chloroform as the extraction solvent is 5% or more.
[0040] A 20th aspect of the present invention is the particle according to any one of the first to nineteenth aspects, which is used for forming a Pickering emulsion.
[0041] The 21st embodiment of the present invention is a method for producing particles described in any one of the above-mentioned embodiments 1 to 20, wherein the method comprises: a step of polymerizing a hydrophobic monomer in the presence of a cationic free radical polymerization initiator and an emulsifier; a step of polymerizing a hydrophilic monomer separately from the above-mentioned hydrophobic monomer or after the polymerization of the hydrophobic monomer is completed; and a step of combining or associating the polymerized hydrophobic monomer with the polymerized hydrophilic monomer.
[0042] A 22nd aspect of the present invention is the particle according to any one of the first to 20th aspects, comprising a polymer having a hydrophobic portion and a hydrophilic portion.
[0043] The 23rd aspect of the present invention is the particle according to the 22nd aspect, wherein the number average molecular weight of the polymer having the hydrophobic part and the hydrophilic part is 1,000 to 500,000.
[0044] The 24th aspect of the present invention is the particle according to the 22nd or 23rd aspect, wherein the polymer having the hydrophobic part and the hydrophilic part has a glass transition temperature of 30° C. or more and 200° C. or less.
[0045] A 25th aspect of the present invention is the particle according to any one of the first to 20th or twenty-second to 24th aspects, wherein the hydrophobic monomer is at least one selected from the group consisting of methyl methacrylate, styrene, and butyl acrylate.
[0046] The 26th aspect of the present invention is the particle according to any one of the 20th or 22nd to 25th aspects, wherein the Pickering emulsion is an emulsion for application to the skin.
[0047] A 27th aspect of the present invention is the particle according to any one of the 20th or 22nd to 26th aspects, wherein the Pickering emulsion contains an aromatic compound.
[0048] The 28th aspect of the present invention is the particle according to the 27th aspect, wherein the aromatic compound is an ultraviolet absorber or an antiseptic.
[0049] The 29th aspect of the present invention is the particle according to any one of the 20th or 22nd to 28th aspects, wherein the Pickering emulsion is a Pickering emulsion that does not allow the aromatic compound contained in the Pickering emulsion to penetrate into the skin.
[0050] The 30th embodiment of the present invention is the particle described in the above-mentioned 13th embodiment, wherein the above-mentioned hydrophobic monomer unit and the above-mentioned hydrophilic monomer unit are bonded by a covalent bond, and a part or all of the surface of the above-mentioned hydrophobic part is directly covered by the polymer of the above-mentioned hydrophilic monomer, and the thickness of the layer of the polymer of the above-mentioned hydrophilic monomer is 0.001nm~200nm.
[0051] According to the present invention, it is possible to provide particles that can form a stable emulsion composition without using a surfactant and have high versatility. The particles of the present invention can also be used to form a Pickering emulsion, and can be used universally in the fields of cosmetics and pharmaceuticals that come into direct contact with the human body. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] [ Figure 1 ] is a schematic comparison diagram of surfactant-based emulsions and Pickering emulsions.
[0053] [ Figure 2 ] are microscope images of the emulsion compositions prepared in Examples 1 to 4 obtained by fluorescence observation using a 100x oil immersion objective.
[0054] [ Figure 3 ] is a diagram showing the results of interfacial tension measurement of the dispersions of Production Examples 1 and 4 using the hanging drop method.
[0055] [ Figure 4 ] is a figure showing the results of analyzing the dry powders obtained by washing, concentrating, freezing and drying the dispersions of Production Examples 1 and 4 using Fourier transform infrared spectroscopy (FT-IR).
[0056] [ Figure 5 ] is a figure showing the results of analyzing the dry powders obtained by washing, concentrating, freezing and drying the dispersions of Production Examples 1 and 4 using Fourier transform infrared spectroscopy (FT-IR).
[0057] [ Figure 6 ] is a figure showing the results of analyzing the dry powders obtained by washing, concentrating, freezing and drying the dispersions of Production Examples 1 and 4 using Fourier transform infrared spectroscopy (FT-IR). DETAILED DESCRIPTION
[0058] Hereinafter, the mode for implementing the present invention will be described in detail with reference to the drawings. It should be noted that the embodiments shown below are described for illustrative purposes, and the following description in the embodiments should not be interpreted as limiting the words of the claims.
[0059] <particle>
[0060] The particles of this embodiment, which are an example of the particles of the present invention, have: a hydrophobic portion containing a hydrophobic monomer unit and having a cationic group; and a hydrophilic portion containing a predetermined hydrophilic monomer unit. The particles of this embodiment are preferably used to form a Pickering emulsion. The particles of this embodiment have storage stability and can form a stable emulsion composition without using a surfactant. In addition, the particles of this embodiment have high versatility and can also be used to form a Pickering emulsion.
[0061] In addition, the particles of this embodiment also have a good texture and can be generally used in the fields of cosmetics and pharmaceuticals that come into direct contact with the human body. The emulsified composition formed using the particles of this embodiment can be prepared without using an ultrasonic treatment device, a homogenizer, or other industrial device that generates a strong external force, and does not necessarily require a heat treatment for stabilizing the dispersed state. Therefore, by using the particles of this embodiment, it is also possible to contribute to reducing the environmental load when preparing the emulsified composition.
[0062] [Hydrophobic part]
[0063] As described above, the hydrophobic portion includes a hydrophobic monomer unit, and can take the form of a polymer obtained by polymerizing such a hydrophobic monomer unit as the main constituent monomer. Such a polymer can be obtained by any homopolymerization or copolymerization, as long as it is within the scope of obtaining the effect of the present invention. As the "hydrophobic monomer unit", for example, a monomer unit obtained by a monomer with an ethylenically unsaturated double bond can be cited. Here, as a monomer with an ethylenically unsaturated double bond, a polymerizable monomer with a carbon-carbon double bond in the molecule can be cited, more specifically, (meth) acrylic acid monomer units, styrene monomer units, etc. can be cited.
[0064] Here, as the (meth) acrylic acid monomer unit, there can be enumerated a monomer unit having an alkyl ester group with a carbon number of 1 or more and 6 or less, and derived from a (meth) acrylic acid alkyl group. Here, as the alkyl ester group with a carbon number of 1 or more and 6 or less, there can be enumerated a methyl ester group, an ethyl ester group, a n-propyl ester group, a n-butyl ester group, a n-pentyl ester group, and a n-hexyl ester group. With regard to these alkyl ester groups, as required, more than one hydrogen atom of the alkyl group constituting the above-mentioned alkyl ester group can be substituted by a hydroxyl group. As the above-mentioned alkyl ester group, from the viewpoint of making the storage stability of the particles sufficient, it is more preferably that the carbon number is 1 or more and 4 or less.
[0065] As such (meth)acrylic acid alkyl, methyl methacrylate (MMA), butyl methacrylate (BMA), 2-hydroxyethyl methacrylate (HEMA) are preferably used, and methyl methacrylate is more preferably used. When these monomers are used, the storage stability of the obtained particles is improved, and the emulsification ability of the particles is further improved.
[0066] In addition, when the (meth)acrylic acid-based monomer unit has an acidic group such as a carboxyl group, the carboxyl group may be in the form of a salt, for example, a sodium salt or a potassium salt.
[0067] Examples of the styrene monomer units include styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, ethylstyrene, isobutylstyrene, tert-butylstyrene, o-bromostyrene, m-bromostyrene, p-bromostyrene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, etc. Among these, styrene is preferably used from the viewpoint of providing sufficient storage stability and emulsifying ability of the obtained particles.
[0068] When the hydrophobic part including a hydrophobic monomer unit and having a cationic group is prepared using the above-mentioned monomers, it is usually sufficient to radically polymerize the above-mentioned monomers.
[0069] [Cationic Group]
[0070] The cationic group possessed by the hydrophobic part of the particle of the present embodiment is usually assumed to be a cationic group derived from a cationic radical polymerization initiator, but it is not limited to the cationic group derived from a cationic radical polymerization initiator, and can be cited from any compound or polymerized unit that can import any cationic group into the hydrophobic part terminal or the hydrophobic part. As a specific example of such a cationic group, primary amino, secondary amino, tertiary amino, quaternary ammonium, imidazolyl, imidazolium, pyridyl, pyridinium, piperidyl, piperidinium, pyrrolidinium, pyrrolidinium, phosphonium etc. can be cited. However, in the present embodiment, as a cationic group, it is particularly preferred to use a cationic group that can be introduced into the cationic group at the end of the hydrophobic part by using a cationic radical polymerization initiator as a polymerization initiator to make hydrophobic monomers polymerized. By using a cationic radical polymerization initiator, the following state can be formed: the end structure derived from the cationic radical polymerization initiator is bonded to the monomer unit at the end of the hydrophobic part with a covalent bond. In the present embodiment, the core portion includes a hydrophobic portion, and a cationic group is disposed on the surface of the core portion or in the vicinity thereof, so that the emulsification ability of the particles can be improved.
[0071] (Cationic radical polymerization initiator)
[0072] As the cationic radical polymerization initiator that can be used in the present embodiment, an initiator that can achieve both safety after polymerization and reactivity as a radical polymerization initiator can be generally used. More specifically, it is preferred to use an initiator selected from 2,2'-[diazene-1,2-diylbis(propane-2,2-diyl)]bis(1,3-dimethyl-4,5-dihydro-1H-imidazol-3-ium)=bis(trifluoromethanesulfonate) salt (ADIP), 2,2'-[diazene-1,2-diylbis(propane-2,2-diyl)]bis(1,3-dimethyl-4,5-dihydro-1H-imidazol-3-ium)=bis(trifluoromethanesulfonate) salt (ADIP), One or more selected from the group consisting of 2,4-dihydro-4,5-dihydro-1H-imidazol-3-ium)=dichloride (ADIP-Cl), 2,2'-azobis(2-methylpropionamidine) dihydrochloride (V-50, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride (VA-044, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and 2,2'-azobis[2-(2-imidazolin-2-yl)propane] (VA-061, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.). By using these cationic radical polymerization initiators, the emulsification ability of the obtained particles becomes better.
[0073] It should be noted that, as a free radical polymerization initiator that can be used in the present embodiment, for example, a cationic free radical polymerization initiator represented by the general formula (III) can be cited. It should be noted that, for further details about the following cationic free radical polymerization initiator, for example, refer to Japanese Patent Publication No. 2017-051113. The content of this document is incorporated as a part of this specification by reference. It should be noted that, as a specific example of a cationic free radical polymerization initiator represented by the general formula (III), the above-mentioned ADIP and ADIP-Cl can be cited. By using ADIP and ADIP-Cl, the particles of the present embodiment can be prepared under milder reaction conditions, and the reduction in the storage stability of the particles caused by damage such as heating during the preparation of the particles can also be suppressed. In addition, by using ADIP and ADIP-Cl, the particles of the present embodiment can be prepared under milder reaction conditions as described above, so it can also contribute to the environmental load during synthesis.
[0074] [Chemical formula 3]
[0075]
[0076] [Wherein,
[0077] Y represents a single bond or CR 85 ,
[0078] Z represents a single bond or CR 86 ,
[0079] R 72 , R 73 , R 75 , R 76 , R 77 , R 78 , R 85 and R 86 Each independently selected from a hydrogen atom, C 1-6 Alkyl, C 1-6 Alkoxy, C 1-6 The group consisting of alkylcarbonyl, phenyl and hydroxyl, wherein the above C 1-6 Alkyl, C 1-6 Alkoxy, C 1-6 Alkylcarbonyl and phenyl can also be selected from C 1-6 Alkyl, C 1-6 Alkoxy, C 1-6 substituted with 1 or 2 substituents selected from the group consisting of alkylcarbonyl, phenyl and hydroxyl,
[0080] R 72 and R 73 They may also each independently represent a C substituted by adamantyl or Si(OCH3)2(CH3) 1-6Alkyl, or R 75 and R 76 , or R 77 and R 78 Can form -(CH2)3-5- together,
[0081] R 81 , R 82 , R 83 , and R 84 To choose free C 1-4 Alkyl, C 1-4 Alkylcarbonyl and C 1-3 The substituents in the group consisting of alkoxy, wherein the above C 1-4 The alkyl group may be replaced by a C 1-3 Alkoxy substitution, and
[0082] R 71 and R 74 Each independently is C 1-3 Alkyl, X f - as counter anion]
[0083] The so-called "counter anion" in the cationic radical polymerization initiator of the above formula (III) is not particularly limited as long as it is an anion commonly used as a counter anion of an organic compound in the field of organic chemical technology, for example, including halide anions (chloride ions, bromide ions, fluoride ions, iodide ions), conjugate bases of organic acids (such as acetate ions, citrate ions, trifluoroacetate ions), nitrate ions, sulfate ions, carbonate ions, etc. As preferred counter anions in the present embodiment, for example, triflate, chloride ions, nitrate ions, etc. can be cited. Among these, from the viewpoint of significantly improving the storage stability of the dispersion of the particles comprising the present embodiment, improving the yield of the particles when preparing the particles of the present embodiment, and being able to improve the manufacturing cost, it is preferably chloride ions, acetate ions and citrate ions, and more preferably chloride ions.
[0084] [Hydrophilic part]
[0085] The hydrophilic part of the particle of the present embodiment more specifically comprises a hydrophilic monomer unit represented by the following formula (I), and can be in the form of a polymer obtained by polymerizing such a hydrophilic monomer unit as a main constituent monomer. Such a polymer can be obtained by any of homopolymerization or copolymerization, as long as it is within the scope of obtaining the effect of the present invention.
[0086] [Chemical formula 4]
[0087]
[0088] It should be noted that the hydrophilic monomer unit represented by the above formula (I) is not particularly limited, and can generally be obtained by polymerizing vinyl acetate using a free radical polymerization reaction and saponifying the acetate group. Therefore, in the present embodiment, although the hydrophilic part must have the hydrophilic monomer unit represented by the above formula (I), it is not limited to that all the monomer units of the above hydrophilic part are represented by the above formula (I). More specifically, the above hydrophilic part includes a monomer unit represented by the following formula (II) derived from vinyl acetate and a monomer unit represented by the above formula (I). From the perspective of improving the storage stability and emulsification ability of the particles themselves and making the storage stability of the emulsion composition formed using the particles good, the ratio of the above hydroxyl group (sometimes simply described as "saponification degree" in the present invention) relative to the total number of acetic acid groups in the monomer unit represented by the following formula (II) and the hydroxyl group in the monomer unit represented by the above formula (I) can be set to 99%, 98% or 96%, and the lower limit can be set to 70%, 75% or 78%. In addition, the "saponification degree" is preferably 70% to 99%, more preferably 75% to 98%, and even more preferably 78% to 96%. By adjusting the "saponification degree", the degree of hydrophilicity of the hydrophilic part of the particle of the present embodiment can be adjusted, so it is preferred to appropriately adjust the above-mentioned "saponification degree" according to the purpose of use of the particle of the present embodiment.
[0089] [Chemical formula 5]
[0090]
[0091] [Core of particle]
[0092] The particles of this embodiment expose organic groups at least on the surface, and the core may contain only organic groups, but is not limited to containing only such organic groups, and may also contain inorganic materials. In the case where the core of the particles of this embodiment contains inorganic materials, a polymer containing a hydrophobic monomer unit may be bound or associated to the surface of the inorganic substance in the core.
[0093] [Crosslinking monomer]
[0094] As the organic monomer unit constituting the core, a cross-linkable monomer unit can be used. In such a manner, as one of the monomers for preparing the particles of the present embodiment, a cross-linkable monomer can be partially used. As a specific example of such a cross-linkable monomer, a monomer commonly used as a cross-linking agent containing two or more ethylenically unsaturated double bonds in the molecule can be cited. However, in the present embodiment, such a cross-linkable monomer may not be used. In the case of using such a cross-linkable monomer, from the viewpoint of making the storage stability of the particles sufficient, relative to the monomer constituting the hydrophobic part and the monomer constituting the hydrophilic part, each in molar conversion, usually, the upper limit of the cross-linkable monomer can be set to 20%, 10% or 5%, and the lower limit can be set to 0.1% or 3%, and its content can be set within the range of 0.1% to 20%, preferably 3% to 10%, and more preferably 5% to 5%. Specific examples of such crosslinking monomers include N,N'-methylenebisacrylamide, N,N'-ethylenebisacrylamide, N,N'-methylenebismethacrylamide, N,N'-ethylenebismethacrylamide, ethylene glycol diacrylate, ethylene glycol dimethacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, and divinylbenzene.
[0095] [Combination of hydrophobic part and hydrophilic part]
[0096] In the particles of the present embodiment, from the viewpoint of making the emulsification ability brought by the particles better, it is preferred that the surface of the core of the particles is hydrophobic, and part or all of it is directly or indirectly coated with a hydrophilic monomer or its polymer. More specifically, the hydrophobic monomer unit and the hydrophilic monomer unit can be bonded by covalent bonds (the "direct coating" method), and the hydrophobic monomer unit and the hydrophilic monomer unit can also be bonded by intermolecular forces (the "indirect coating" method).
[0097] In addition, when the hydrophobic monomer unit and the hydrophilic monomer unit are bonded by a covalent bond, the polymer formed by the covalent bonding of the two can be a block copolymer or a graft copolymer. In the case of a graft copolymer, the storage stability of the particles is particularly good. Therefore, the polymer formed by the covalent bonding of the hydrophobic monomer unit and the hydrophilic monomer unit is more preferably a graft copolymer.
[0098] In addition, when the hydrophobic monomer unit and the hydrophilic monomer unit are bonded by intermolecular force, the bonding by intermolecular force is preferably brought about by heat treatment from the viewpoint of making the storage stability of the particles and the emulsification ability brought about by the particles better. As the heat treatment in this case, for example, a heat treatment can be performed at a temperature of 20°C to 100°C, more specifically 30°C to 80°C for 30 minutes to 480 minutes.
[0099] It should be noted that the particles of the present embodiment are not limited to particles in which the hydrophobic monomer units and the hydrophilic monomer units are bonded only by covalent bonds or particles in which the hydrophobic monomer units are bonded only by intermolecular forces, but a part of the hydrophobic monomer units may be bonded to the hydrophilic monomer units by covalent bonds, and the remaining hydrophobic monomer units may be bonded to the hydrophilic monomer units by intermolecular forces. As for the existence ratio of the hydrophobic monomer units bonded to the hydrophilic monomer units by covalent bonds, from the viewpoint of making the emulsification ability brought by the particles good, the upper limit may be set to 90%, 70% or 60% relative to the whole hydrophobic monomer units bonded to the hydrophilic monomer units, and the lower limit may be set to 10%, 30% or 40%, preferably 10% or more and 90% or less, more preferably 30% or more and 70% or less, and further preferably 40% or more and 60% or less.
[0100] In the above-described manner, from the viewpoint of improving the storage stability of the particles and the emulsifying ability brought about by the particles, with respect to the ratio of the hydrophobic portion to the hydrophilic portion, the upper limit of the mass corresponding to the hydrophilic portion can be set to 6 parts by mass or 4 parts by mass, and the lower limit can be set to 1 part by mass or 3 parts by mass, relative to 100 parts by mass of the mass corresponding to the hydrophobic portion, preferably equivalent to more than 1 part by mass and less than 6 parts by mass, and more preferably more than 3 parts by mass and less than 4 parts by mass.
[0101] [Molecular weight]
[0102] In the particle of the present embodiment, the molecular weight of the polymer (polymer with hydrophobic part and hydrophilic part) or the molecular weight of the single molecule in the case of the hydrophobic part of the form of polymer and the hydrophilic part of the form of polymer by covalent bonding, or by the total value of the molecular weight of the single molecule of the hydrophobic part and the single molecule of the hydrophilic part in the case of non-covalent bonding is not particularly limited, for example, it can be calculated in the form of the number average molecular weight converted by polystyrene when the particle is dissolved in an organic solvent such as chloroform and gel permeation chromatography is measured. At this time, when the hydrophobic part of the form of polymer is bonded with the hydrophilic part of the form of polymer in the form of non-covalent bonding, as required, the operation of separating the hydrophobic part from the hydrophilic part can be implemented. From the viewpoint of making the storage stability of the particles good, the upper limit of the number average molecular weight of the polymer having the hydrophobic part and the hydrophilic part can be set to 500,000, 30,000, 20,000 or 10,000, and the lower limit can be set to 1,000, 10,000 or 50,000. As for the number average molecular weight of the polymer having the hydrophobic part and the hydrophilic part, from the viewpoint of making the storage stability of the particles good, it is preferably 1,000 to 500,000, 1,000 to 100,000, 5,000 to 20,000, 10,000 to 500,000, 50,000 to 30,000 or 50,000 to 30,000. In addition, the ratio of the number average molecular weight to the weight average molecular weight, i.e., the molecular weight distribution, is preferably in the range of 1.05 to 5, and more preferably in the range of 1.05 to 1.7. In addition, in the present embodiment, the relative ratio of the molecular weight of only the hydrophobic part and the molecular weight of only the hydrophilic part per unit particle is preferably 1 to 6 relative to the hydrophobic part 100. By making the above relative ratio within the above range, the emulsification ability of the particles of the present embodiment can be improved, and the storage stability of the particles of the present embodiment can be improved.
[0103] [Glass transition temperature]
[0104] The glass transition temperature of the polymer having a hydrophobic portion and a hydrophilic portion may have an upper limit of 200°C, 150°C or 100°C and a lower limit of 30°C, 40°C or 45°C from the viewpoint of improving the storage stability of the emulsion composition.
[0105] The glass transition temperature of a polymer can be measured using differential scanning calorimetry (DSC). The specific measurement method of the DSC method is in accordance with the method described in JIS K 7121 (1987).
[0106] It should be noted that, with regard to the glass transition temperature of the polymer, for example, polystyrene may be 100°C, polymethyl methacrylate may be 105°C, polyisopropyl methacrylate may be 83°C, polycyclohexyl methacrylate may be 107°C, polyphenyl methacrylate may be 110°C, polyacrylic acid may be 101°C, poly N,N-dimethylacrylamide may be 121°C, polydimethylitaconate may be 100°C, and polydimethylfumarate may be 100°C.
[0107] [Pickering Lotion]
[0108] From the viewpoint of texture and safety, the Pickering emulsion is preferably applied to the skin.
[0109] In this embodiment, the Pickering emulsion preferably contains an aromatic compound because the risk related to safety to the human body can be reduced while maintaining the stability of the emulsion.
[0110] Aromatic compounds include cyclic unsaturated organic compounds represented by benzene, as well as aromatic hydrocarbons composed only of hydrocarbons and heteroaromatic compounds containing elements other than carbon in the ring structure).
[0111] The Pickering emulsion is preferably a Pickering emulsion that does not allow the aromatic compound contained in the Pickering emulsion to penetrate into the skin. This is because the Pickering emulsion can reduce the content of the surfactant required for emulsification, and further, can inhibit the aromatic compound caused by the surfactant from penetrating into the skin.
[0112] The aromatic compound is not particularly limited, but is preferably an ultraviolet absorber or an antiseptic.
[0113] The aforementioned ultraviolet absorber is not particularly limited, and examples thereof include ethylhexyl methoxycinnamate, octocrylene, dimethicone diethyl benzalmalonate, polysilicone-15, tert-butyl methoxydibenzoylmethane, ethylhexyl triazone, diethylaminohydroxybenzoyl hexyl benzoate, bis-ethylhexyloxyphenol methoxyphenyl triazine, benzophenone-3, methylene bisbenzotriazolyl tetramethylbutylphenol, phenylbenzimidazole sulfonic acid, homosalate, ethylhexyl salicylate, and the like. The ultraviolet absorber used in the present invention may be formulated in one kind or in combination of two or more kinds. The aforementioned ultraviolet absorber is not particularly limited, and from the viewpoint of the stability of the emulsion, ethylhexyl methoxycinnamate, octocrylene, and diethylaminohydroxybenzoyl hexyl benzoate are preferred.
[0114] The preservative is not particularly limited, and examples thereof include phenoxyethanol, benzoic acid and its salts, salicylic acid and its salts, phenol and its salts, dehydroacetic acid and its salts, parabens (e.g., methylparaben, ethylparaben, butylparaben, etc.), parachlorometacresol, hexachlorophene, resorcinol, isopropylmethylphenol, o-phenylphenol, benzalkonium chloride, chlorhexidine hydrochloride, chlorhexidine gluconate, alkylisoquinoline bromide, triclocarban, halocarban, photosensitive element No. 201, trichlorohydroxydiphenyl ether (triclosan), methylchloroisothiazolinone / methylisothiazolinone solution, bisabolol, alkyldiaminoethylglycine hydrochloride, trichlorosalicylanilide (TCSA), tribromosalicylanilide (TBS), etc. The preservative used in the present invention may be blended alone or in combination of two or more.
[0115] [Other properties of particles]
[0116] The average zeta potential of the particles of this embodiment is calculated by electrophoresing a composition mainly containing the particles, measuring the migration velocity of the particles using laser Doppler velocimetry (e.g., Zetasizer Nano ZSP manufactured by Malvern Panalytical), and applying Henry's equation shown below to the migration velocity of the particles.
[0117] [Mathematical formula 1]
[0118]
[0119] Here, U represents electrophoretic mobility, ε represents the relative dielectric constant of the particle dispersion medium, z represents Zeta potential, f(Ka) represents Henry's coefficient, and η represents the viscosity of the particle dispersion medium.
[0120] In more detail, with reference to the determination method of the average Zeta potential recorded in the embodiment. The upper limit of the average Zeta potential of the particle of the present embodiment can be set to +60mV or +40mV, and the lower limit can be set to +10mV or +30mV, preferably more than +10mV +60mV or less, more preferably more than +30mV +40mV or less. The present invention is not subject to any theoretical constraint, but it is inferred that when the average Zeta potential of the particle of the present embodiment is in the above-mentioned range, the particles repel each other, thus suppressing the aggregation of the particles, so the storage stability of the particles improves. It is inferred in addition that when the average Zeta potential of the particle of the present embodiment is in the above-mentioned range, it is easy to be adsorbed on the interface of the hydrophilic medium and the hydrophobic medium in the emulsified composition, so the emulsifying ability brought by the particles becomes good, improves the storage stability of the emulsified composition.
[0121] In addition, the cumulative average diameter of the particles of the present embodiment is calculated by measuring the scattered light intensity from the particles performing Brownian motion in the dispersion medium in the dispersion containing the particles, and the intensity changes over time (dynamic light scattering method). From the viewpoint of improving the storage stability of the particles, improving the emulsification ability brought by the particles, and improving the storage stability of the emulsified composition, the upper limit of the cumulative average diameter of the particles of the present embodiment can be set to 500nm or 450nm, and the lower limit can be set to 100nm or 150nm, preferably 100nm or more and 500nm or less, and more preferably 150nm or more and 450nm or less.
[0122] In addition, from the viewpoint of improving the emulsification ability of the particles and ensuring sufficient storage stability of the emulsified composition, the interfacial tension value (T ) between the aqueous dispersion containing 0.01% by mass of the particles of the present embodiment and decamethylcyclopentasiloxane is 0.01% by mass. 0.01 ), and the difference (T1) between the interfacial tension value (T2) of the aqueous dispersion containing 1% by mass of the particles of the present embodiment and decamethylcyclopentasiloxane. 0.01 -T1) is preferably 10 mN / m or more, more preferably 15 mN / m or more. In addition, from the viewpoint of improving the emulsification ability brought by the particles and improving the storage stability of the emulsified composition, the interfacial tension value (T1) between the aqueous dispersion containing 1% by mass of the particles of the present embodiment and decamethylcyclopentasiloxane is preferably 25 mN / m or less, more preferably 20 mN / m or less, and further preferably 10 mN / m or more and 18 mN / m or less.
[0123] It should be noted that, in the present embodiment, the interfacial tension can be measured by the pendant drop method. When measuring, a contact angle meter (trade name: DMo-502, manufactured by Kyowa Interface Science Co., Ltd.) can be used, and as the surrounding phase, decamethylcyclopentasiloxane (cyclopentasiloxane, commonly known as "D5", with a specific gravity of 0.96 g / cm 3 ), as water used in the aqueous dispersion, purified water, ion exchange water, pure water, etc. can be used. At this time, the measurement conditions of room temperature (25° C., etc.) and humidity 45%±10% can be adopted.
[0124] In addition, in the present embodiment, the residual rate of the insoluble fraction of the particles of the present embodiment after extraction by a Soxhlet extractor using chloroform as an extraction solvent is preferably 5% or more, more preferably 6% or more and 15% or less. By adjusting the residual rate of the insoluble fraction to within the above range, the ratio of the hydrophobic part to the hydrophilic part of the particles of the present embodiment can be appropriately adjusted, the emulsification ability brought by the particles of the present embodiment becomes good, and the storage stability of the composition containing the particles is improved.
[0125] [Morphology and properties of the composition including particles]
[0126] The composition comprising the particles of the present embodiment can be a dispersion formed by being roughly uniformly dispersed in a dispersion medium, or it can be a powder composition, and its form and properties are not particularly limited. However, from the viewpoint of reducing the complexity of various process operations during manufacture, the composition comprising the particles of the present embodiment is preferably a dispersion formed by being roughly uniformly dispersed in a dispersion medium. As the dispersion medium, the reaction solvent after synthesizing the particles can be directly left as a dispersion medium, or the reaction solvent can be distilled off as needed, and other solvents are added as dispersion medium. From the viewpoint of reducing the complexity of various process operations during manufacture, it is preferred that the reaction solvent after synthesizing the particles is directly used as a dispersion medium. In the case where the reaction solvent after the particle synthesis is directly used as a dispersion medium, from the viewpoint of improving storage stability and reducing irritation, it is preferred to remove unreacted monomers. When removing unreacted monomers, its specific implementation method is not particularly limited, and from the viewpoint of reducing the complexity of various operations during manufacture, improving storage stability, and reducing irritation, it is preferred to add a polymerization initiator in the composition comprising unreacted monomers. In this case, the additional addition amount of the polymerization initiator is preferably 0.1 times to 1 times relative to the addition amount during particle synthesis. The present invention is not subject to any theory, but it is speculated that by adding polymerization initiator additionally, unreacted monomers become polymers of dimers or more by polymerization reaction, and on the other hand, the additional polymerization initiator decomposes in the reaction solvent even if it remains and becomes a stable decomposition product. It should be noted that, from the viewpoint of reducing the manufacturing cost of particles, the solid content mass in the dispersion of particles comprising the present embodiment is preferably 1% by mass or more relative to the dispersion as a whole, and more preferably 10% by mass or more and 50% by mass or less.
[0127] As the dispersion medium for dispersing the particles of the present embodiment, it is not particularly limited. From the viewpoint of improving storage stability and reducing irritation, it is preferred to use an aqueous medium, and more preferably water and an alcoholic medium. As a specific example of an alcoholic medium, low molecular diols and triols with carbon atoms of less than 6 such as lower alcohols such as methanol, ethanol and isopropanol, and 1,3-butylene glycol, glycerol, ethylene glycol and propylene glycol can be cited. Among these, from the viewpoint of improving storage stability, it is preferably selected from more than one of the group consisting of water and lower alcohols, preferably a medium containing at least water.
[0128] (Other additives)
[0129] In the composition comprising the particles of the present embodiment, in addition to comprising various active ingredients (for example, cosmetic active ingredient ingredients; whitening agent, cell activator, anti-inflammatory agent, blood circulation promoter, skin astringent, anti-seborrheic agent, etc.) that can be added as needed, various additives conventionally used in the purposes can also be appropriately contained as optional components according to the purposes of the composition in the scope that does not damage the purpose of the present invention. As the additive, for example, antioxidant, rust inhibitor, gelling agent, dispersant, thickener, oil agent, alcohol, ether, water, pH adjusting agent, stabilizer, bactericide, mildew inhibitor, preservative, coloring agent, chelating agent, humectant, pearlescent agent, fragrance, ultraviolet absorber, ultraviolet scattering agent, etc. can be enumerated.
[0130] <Method for producing particles>
[0131] The method for producing the particles of the present embodiment is not particularly limited, and examples thereof include polymerizing the hydrophobic monomer and the hydrophilic monomer separately or successively (i.e., polymerizing the hydrophilic monomer separately from the hydrophobic monomer; or polymerizing the hydrophilic monomer after the completion of the polymerization of the hydrophobic monomer), and then forming particles, etc. The method for producing the particles of the present embodiment is not particularly limited, and for example, has the particle forming step shown below, and may include a modification step and other steps.
[0132] [(1) Particle Forming Process]
[0133] The particle formation step is not particularly limited, and for example, there can be mentioned a process of particle formation while polymerizing monomer components such as hydrophobic monomers by emulsion polymerization, suspension polymerization, dispersion polymerization, etc. It should be noted that during the polymerization, the polymerization reaction is preferably carried out in the presence of an emulsifier. In addition, the particle formation step can be a process of particle formation of the obtained reaction product by phase inversion emulsification, suspension method, etc. after the monomer components are polymerized by solution polymerization, etc.
[0134] However, from the viewpoint of reducing the complexity of manufacturing, it is preferred to polymerize the monomer components while particle-forming the process, more preferably emulsion polymerization, suspension polymerization or dispersion polymerization, and further preferably emulsion polymerization. In addition, in the emulsion polymerization, from the viewpoint that the surface of the hydrophobic part that becomes the core is not mixed with impurities such as emulsifiers, and it is not easy to affect the following modification process that can be performed later, it is preferred to adopt soap-free emulsion polymerization. There is no particular limitation on the specific implementation method of the soap-free emulsion polymerization, and it can be implemented using known methods. For example, it can be implemented by carrying out emulsion polymerization of the monomer components in the presence of a polymerization initiator without using emulsifiers such as surfactants, polymer emulsifiers, and reactive surfactants.
[0135] In the particle formation process, the solvent used is not particularly limited, and an aqueous medium can be cited. From the viewpoint of improving the storage stability of the particles, the aqueous medium used in the particle formation process can contain water or alcohol. The reaction temperature during the particle formation process is preferably set to a temperature below the boiling point of the solvent.
[0136] [(2) Modification step]
[0137] In the above modification step, for example, a part or the whole of the surface of the hydrophobic part is directly or indirectly coated with a hydrophilic monomer or a polymer of the above hydrophilic monomer. Alternatively, in the above modification step, it can also be described as a step of combining or associating the polymerized hydrophobic monomer with the polymerized hydrophilic monomer.
[0138] As a method of directly covering the surface of the hydrophobic part with the above-mentioned hydrophilic monomer, for example, there can be cited a method of bonding the hydrophobic monomer unit present on the surface of the hydrophobic part to the above-mentioned hydrophilic monomer unit by covalent bonds. More specifically, there are the following methods: a method of covalently bonding an atomic group derived from the polymer of the above-mentioned hydrophilic monomer to an atomic group derived from the hydrophobic monomer unit present on the surface of the core part; a method of covalently bonding vinyl acetate as a hydrophilic monomer to an atomic group derived from the hydrophobic monomer unit present on the surface of the core part, further polymerizing vinyl acetate therewith, and then hydrolyzing the ester of the polyvinyl acetate part to saponify it to form a hydrophilic part. However, as a method of directly covering the surface of the hydrophobic part with the above-mentioned hydrophilic monomer, from the viewpoint of achieving good emulsification ability, it is preferred to adopt a method of covalently bonding a polymer containing the above-mentioned hydrophilic monomer unit to an atomic group derived from a hydrophobic monomer unit present on the surface of the core part. More preferably, the polymer containing the above-mentioned hydrophilic monomer unit is polyvinyl alcohol, and further preferably, the covalent bond is a carbon-carbon covalent bond formed by a free radical reaction using a free radical polymerization initiator.
[0139] In the case where the surface of the hydrophobic portion is directly coated with the hydrophilic monomer or the like, the thickness of the layer of the polymer containing the hydrophilic monomer unit can be calculated. Specifically, the average particle diameter of the method in which the polymer containing the hydrophilic monomer unit is covalently bonded is subtracted from the average particle diameter of the method in which the polymer containing the hydrophilic monomer unit is not covalently bonded, and then multiplied by 0.5 to calculate. In this calculation, the average particle diameter is obtained in the following manner.
[0140] First, 20 mL of a polymer containing a hydrophilic monomer unit was dispensed into a 50 mL Nunc tube and centrifuged at 15,300 × g for 15 minutes using a centrifuge. After centrifugation, the supernatant was removed, 20 mL of Elix water was added, and then mixed and stirred with a vortex mixer until the precipitate was evenly dispersed, and the operation was repeated 3 times for washing. The sample after 3 washes was centrifuged again, and then Elix water was added to redisperse it in a manner that the solid content mass became 0.001 mass %, and a sample for average particle size measurement was prepared.
[0141] Next, the average particle size of the sample prepared above is measured using an appropriate molecular weight measuring device. During the measurement, analysis software can be used appropriately as needed. The relative dielectric constant required for the measurement is the value of water at 25°C (78.5), the Henry coefficient is 1.5, and the viscosity of the dispersion medium is the value of the viscosity of water at 25°C (0.89 mPa·s). As for the mass of the solid component, each polymer containing a hydrophilic monomer unit is weighed and then heat-dried or freeze-dried, and the mass difference before and after drying is calculated.
[0142] The thickness of the layer of the polymer containing the hydrophilic monomer unit calculated in the above manner is not particularly limited. From the viewpoint of improving storage stability and making the emulsification ability brought by the particles sufficient, the upper limit can be set to 200nm, 100nm, 50nm, 30nm or 20nm, and the lower limit can be set to 0.001nm, 0.01nm, 0.1nm, 1nm or 5nm. From the viewpoint of improving storage stability and making the emulsification ability brought by the particles sufficient, the thickness of the layer of the polymer containing the aqueous monomer unit is preferably 0.001nm to 200nm, more preferably 0.1nm to 50nm, and more preferably 5nm to 20nm.
[0143] As a method for indirectly coating the surface of the hydrophobic part by the above-mentioned hydrophilic monomer, for example, a method can be cited in which the atomic groups contained in the hydrophobic monomer unit present on the surface of the core (hydrophobic part) and the atomic groups contained in the above-mentioned hydrophilic monomer unit interact with each other by using intermolecular forces, electrostatic interactions, etc. At this time, as a result, the hydrophobic part interacts with the above-mentioned hydrophilic part, and since the interaction between the two is easier, any functional group or atomic group can be introduced into the hydrophobic part and / or the above-mentioned hydrophilic part. As a method for using intermolecular forces, electrostatic interactions, etc. to make the atomic groups contained in the hydrophobic monomer unit present on the surface of the hydrophobic part interact with the atomic groups contained in the above-mentioned hydrophilic monomer unit, it is preferred to use a method in which the particles obtained in the (1) particle formation step are added with the polymer containing the hydrophilic monomer unit, and the temperature, pressure, concentration conditions, etc. of the mixed solution are appropriately set while introducing any functional group and atomic group as needed, and more preferably the mixed solution is heated, pressurized or concentrated.
[0144] [Other processes]
[0145] The method for manufacturing particles of the present embodiment may also include other steps in addition to (1) the particle formation step and (2) the modification step. The additional "other steps" are not particularly limited, and examples thereof include a washing step, a concentration step, and a drying step. For example, the washing step, the concentration step, and the drying step may be integrated into at least one of the (1) particle formation step and the (2) modification step, or may be independent (in time or space) of the (1) particle formation step and the (2) modification step.
[0146] In order to reduce the irritation of the composition containing the obtained particles, the method for manufacturing the particles of the present embodiment preferably has a cleaning step. As the medium used in the cleaning step, there is no particular limitation, and an aqueous medium can be used. For example, when the reaction solvent used in the particle formation step is an aqueous medium, the cleaning step can be carried out in the following manner: the particles of the present embodiment are precipitated by centrifugation, the supernatant is removed, and then the above-mentioned aqueous medium is added for redispersion, and the above-mentioned operation is repeated. In addition, when the reaction solvent used in the particle formation step is an organic solvent, it can be carried out in the following manner: an aqueous medium to which salts such as brine are added is mixed in the reaction solvent and stirred, and a separating funnel is used to separate the aqueous phase from the organic phase. The method for manufacturing the particles of the present embodiment can reduce the residual amount of the unreacted free radical polymerization initiator, its decomposition product, and the unreacted monomer in the medium (for example, so that their respective concentrations are less than 100ppm) by having a cleaning step.
[0147] From the viewpoint of fully exerting the emulsifying ability of the particles, the method for producing the particles of the present embodiment preferably has a concentration step for increasing the concentration of the particles in the composition. The concentration step is not particularly limited and can be implemented by precipitating the particles of the present embodiment by centrifugation, removing the supernatant, and then adding a medium with a mass and / or volume smaller than that of the removed supernatant to perform redispersion; or by drying the particles of the present embodiment to form a powder, and then adding a medium with a mass and / or volume smaller than that of the medium removed by drying to perform redispersion, etc.
[0148] In addition, in order to make the state of the particles of the present embodiment into a powder state, the manufacturing method of the particles of the present embodiment preferably has a drying process. The drying process can be implemented by evaporating the medium containing the particles of the present embodiment, drying, etc. As the specific method adopted in the drying process, there is no particular limitation, and hot air drying, infrared drying, fluidized bed drying, spray drying, freeze drying, reduced pressure drying, vacuum drying, etc. can be cited.
[0149] It should be noted that the method for producing particles according to the present embodiment may include only one step of the particle formation step, or may be a multi-step production method including other steps in addition to the particle formation step.
[0150] When the method for manufacturing the particles of the present embodiment is set as a method having only a particle formation step, it is preferred that in the particle formation step, the surface of the core of the particles of the present embodiment is made hydrophobic by appropriately modifying the hydrophobic portion, and at the same time, a part or all of the surface of the core is directly or indirectly covered with a hydrophilic monomer, etc.
[0151] In the case where the method for producing particles of the present embodiment is set as a method having multiple steps including a particle formation step, from the viewpoint of improving storage stability and making the emulsification ability brought by the particles sufficient, it is preferably set as a method having two steps (1) a particle formation step and (2) a modification step. In addition, in the case where the method for producing particles of the present embodiment is set as a method having multiple steps including a particle formation step, it can be set as a method having three or more steps including one or more other steps, the order of each step is arbitrary, and each step can be repeated multiple times. In the case where the method for producing particles of the present embodiment is set as a method having two or more steps (1) a particle formation step and (2) a modification step, it is preferred that a hydrophobic portion (core portion) is formed in the (1) particle formation step, and in the (2) modification step, a part or all of the surface of the hydrophobic portion (core portion) is directly or indirectly coated with a hydrophilic monomer or the like.
[0152] It should be noted that a more specific method for producing the particles is disclosed in detail in the following examples.
[0153] <Use of composition containing particles>
[0154] The use of the composition containing the particles of the present embodiment is not particularly limited, and the composition containing the particles of the present embodiment can be used as cosmetics, pharmaceuticals, quasi-drugs, inks (including inks and pigment dispersions contained in stationery such as writing tools), coatings, etc. The composition containing the particles of the present embodiment can be formulated by appropriately combining various main components / active ingredients and various additives according to the above-mentioned uses.
[0155] In the case of a composition containing the particles of the present embodiment, for example, in the case of cosmetics, pharmaceuticals, or quasi-pharmaceuticals, various commonly used additives may be added to the composition within the range that does not hinder the effects of the present invention. Examples of such additives include antioxidants, gelling agents, thickeners, oils, alcohols, ethers, water, pH adjusters, stabilizers, bactericides, antifungal agents, preservatives, colorants, chelating agents, humectants, pearlescent agents, fragrances, ultraviolet absorbers, ultraviolet scattering agents, and the like.
[0156] It should be noted that, for the sake of clarity, when referring to the use of a composition comprising the particles of the present embodiment as a cosmetic, various skin-beautifying ingredients (e.g., whitening agents, cell activators, anti-inflammatory agents, blood circulation promoters, skin astringents, anti-seborrheic agents, etc.) can be cited as the cosmetic active ingredients.
[0157] Example
[0158] Hereinafter, the present invention will be described in detail with reference to Examples. It should be noted that the Examples shown below are described for the purpose of illustrative description, and the contents of the present invention are not limited to the following Examples in any way.
[0159] <Manufacturing Examples 1 and 2; Synthesis of Polymethyl Methacrylate (PMMA) Dispersion>
[0160] Methyl methacrylate (MMA) and pure water replaced with argon (water purified by Elix Essential UV (Merck Millipore) under the trade name Elix Essential UV; hereinafter, sometimes simply referred to as "Elix water". In addition, the resistivity of Elix water is 5MΩ·cm or more) were added to a 30 mL transparent glass vial (trade name: SV-30, manufactured by Nichiden Rika Glass Co., Ltd.) in a total volume of 30 mL according to the formulation shown in Table 1. As a cationic radical polymerization initiator, 1 mL (23 mg ADIP-Cl, 2 mM) of a methanol (MeOH) solution of ADIP (hereinafter, referred to as ADIP-Cl) whose counter anion is a chloride ion was added, and the mixture was stirred for 14 hours using a strong stirrer in a hot water bath at 60°C to obtain a PMMA dispersion.
[0161] [Table 1]
[0162] Table 1: Synthesis conditions of Preparation Examples 1 and 2
[0163]
[0164] <Manufacturing Examples 3 to 6; Synthesis of PMMA-PVA Dispersions>
[0165] The PMMA dispersion obtained according to the steps of manufacturing examples 1 and 2 was added to a 300mL separable flask with a baffle in a manner that the final solid content mass became 4.8g, and the polyvinyl alcohol with a specified degree of polymerization and saponification recorded in Table 2 of a specified mass was further added, and Elix water was added in a manner that the overall mass became 199g. Then, the solution was heated to 60°C while stirring at a stirring speed of 450rpm. Next, 1mL of 38mg / mL ADIP-Cl solution was added and stirred at a stirring speed of 450rpm for 3 hours at 60°C to obtain a PMMA-PVA dispersion. It should be noted that, with respect to manufacturing examples 3 to 6, it was confirmed that even after being stored at 50°C for 3 months, in the observation of the appearance of the properties, although it was precipitated, it did not become a coarse aggregate, and it was restored to a uniform dispersion state by only gently shaking. Therefore, it is shown that the storage stability of the PMMA-PVA dispersion obtained is good.
[0166] [Table 2]
[0167] Table 2: Synthesis conditions of PPMMA-PVA
[0168]
[0169] <Production Example 7: Synthesis of Fluorescently Labeled PMMA Dispersion>
[0170] 4.5 g of methyl methacrylate (MMA, 1.5 M), 16 mg of 3-(2-benzothiazolyl)-7-(diethylamino)coumarin (commonly known as "coumarin-6", manufactured by Sigma-Aldrich, 1.5 mM), and 24 mL of argon-substituted Elix water were added to a 30 mL transparent glass vial (trade name: SV-30, manufactured by Nippon Rika Glass Co., Ltd.). 900 μL of a methanol (MeOH) solution of ADIP-Cl (23 mg ADIP-Cl, 2 mM) was added, and the mixture was stirred for 14 hours in a hot water bath at 60° C. using a strong stirring bar to obtain a fluorescent labeled PMMA dispersion.
[0171] [Table 3]
[0172] Table 3: Synthesis conditions of fluorescent labeled PMMA emulsion
[0173]
[0174] <Production Example 8: Synthesis of Fluorescently Labeled PMMA-PVA Dispersion>
[0175] Next, the sample obtained in Preparation Example 7 (in a manner of forming 4.8 g of solid content), 667 mg of PVA (trade name: JP-05, manufactured by JAPAN VAM & POVAL CO., LTD., saponification degree: 88 mol%, average polymerization degree: 500), and 164 mL of Elix water replaced with argon were added to a 300 mL separable flask with a baffle. 38 mg of ADIP-Cl (0.5 mM) was added, and the mixture was stirred at 60° C. at a stirring speed of 450 rpm for 3 hours to obtain a fluorescent labeled PMMA-PVA dispersion. Furthermore, the fluorescent labeled PMMA-PVA dispersion was then washed and concentrated.
[0176] [Table 4]
[0177] Table 4: Synthesis conditions of fluorescent labeling PMMA-PVA emulsion
[0178]
[0179] <Production Example 9: Synthesis of PMMA-PVA Dispersion>
[0180] The PMMA dispersion obtained according to the procedure of Production Example 1 was added to a 300 mL separable flask with baffles in such a manner that the final solid component mass became 4.8 g. Further, 2.7 g of PVA (trade name: JMR-3H, manufactured by JAPANVAM&POVAL CO., LTD., saponification degree: 78 mol%, average degree of polymerization: 110) of a specified mass was added, and Elix water was added in such a manner that the total mass became 199 g. Then, while stirring at a stirring speed of 450 rpm, the solution was heated to 60°C. Next, 1 mL of a 38 mg / mL ADIP-Cl solution was added, and the mixture was stirred at a stirring speed of 450 rpm at 60°C for 3 hours to obtain a PMMA-PVA dispersion. It should be noted that, compared with Production Examples 3 to 6, the degree of polymerization of the PVA used in Production Example 9 is small and it has a low saponification degree. Similar to Production Examples 3 to 6, in Production Example 9, it was also confirmed that even after storage at 50°C for 3 months, it did not become large aggregates and returned to a uniform dispersion state only by gently shaking. Therefore, it was shown that the obtained PMMA-PVA dispersion had good storage stability, and at the same time, it was found that PVA with a small degree of polymerization and a low saponification degree could also be used for the synthesis of PMMA-PVA dispersions.
[0181] <Washing and Concentration of PMMA-PVA Dispersion>
[0182] Unreacted PVA may be present in the PMMA-PVA dispersion. Examples of unreacted PVA include PVA in a state not bound to the particles. In addition, from the viewpoint of making the emulsifying ability of the particles better, it is preferable to increase the solid component mass of the PMMA-PVA dispersion. The solid component mass is more preferably 4% by mass or more, further preferably 7% by mass or more, and particularly preferably 10% by mass or more.
[0183] [Washing and Concentration Operations]
[0184] 20 mL of the PMMA-PVA dispersion was dispensed into a 50 mL Nunc tube, and centrifuged at 15,300×g for 15 minutes using a centrifuge (trade name: MX-305, manufactured by TOMY SEIKO Co, Ltd., rotor: AR510-04). The supernatant was removed, 20 mL of Elix water was added, and then the mixture was mixed and stirred using a vortex mixer until the precipitate was uniformly dispersed. The above operation was repeated 3 times for washing. The sample after washing 3 times was centrifuged again, and then Elix water was added in such a manner that the solid component mass became 10% by mass to redisperse it, obtaining a PMMA-PVA concentrated dispersion.
[0185] <Analysis Method>
[0186] The average particle size, dispersion degree (PdI) and average Zeta potential were measured using a particle size, Zeta potential and molecular weight measuring device (trade name: Zetasizer Nano ZSP, manufactured by Malvern Panalytical). The analysis software used was Zetasizer Software 7.12 manufactured by Malvern. The relative dielectric constant required for the measurement of particle size, PdI and Zeta potential was water at 25°C (78.5), the Henry constant was 1.5, and the viscosity of the dispersion medium was the viscosity of water at 25°C (0.89 mPa·s). As for the mass of the solid component, each dispersion was weighed and then subjected to heat drying or freeze drying, and the mass difference before and after drying was calculated. The PVA addition rate was calculated as follows. 1 g of PMMA-PVA dispersion was centrifuged at 20,400×g for 15 minutes. After collecting the supernatant by suction, it was transferred to an empty Eppendorf tube whose mass had been measured in advance and freeze-dried. The mass of PVA remaining in the supernatant was calculated from the mass difference of the Eppendorf tube before and after freeze drying, and the PVA addition amount was calculated by subtracting the mass of PVA remaining in the supernatant from the mass of PVA input during synthesis. As for the PVA addition rate, the value of the PVA addition amount was divided by the value of the PMMA input mass, and the value converted into percentage was expressed as mass %.
[0187] [Mathematical formula 2]
[0188] PVA addition amount = PVA mass input - PVA mass remaining in the supernatant
[0189] PVA addition rate = (PVA addition amount ÷ PMMA input amount) × 100
[0190] [Table 5]
[0191] Table 5: Details of the samples produced
[0192]
[0193] <Experimental Example 1: Preparation of emulsified composition>
[0194] [When the dispersion of the production example is used]
[0195] PMMA or PMMA-PVA dispersion is added to a transparent glass vial (trade name: SV-20, manufactured by Nippon Rika Glass Co., Ltd., capacity 20 mL, 27 mm × 55 mm) in such a way that the solid content is 1% by mass, and 1 g of 1,3-butanediol (BG) and 7 g of mineral oil (trade name: Moresco White P-70, manufactured by MORESCO) are added thereto in such a way that the total mass becomes 10 g (mass ratio of oil: BG: water = 7:2:1, 1% PMMA or PMMA-PVA by mass). A strong stirring bar is used with a magnetic stirrer (trade name: NK-SA03, manufactured by Nakazawa Seisakusho Co., Ltd.). The mixture was stirred at 2000 rpm for 15 minutes. The appearance of the mixture was observed 1 minute after the stirring was completed, and no phase separation was observed, confirming that the mixture was emulsified.
[0196] [In the case of polyvinyl alcohol (PVA)]
[0197] The preparation of an emulsified composition was attempted in the same manner as in [the case of using the dispersion of the production example]. An aqueous solution of PVA (trade name: JP-05, manufactured by JAPAN VAM & POVAL CO., LTD., saponification degree: 88%, average polymerization degree: 500) was prepared, and PVA was added to give 1% by mass, followed by stirring.
[0198] The above results are shown in Tables 6 and 7. In the case of using PVA monomer or particles without PVA addition reaction (Comparative Examples 1 to 4), emulsification was not confirmed. On the other hand, in the case of using particles with addition reaction using PVA (Examples 1 to 5), emulsification was confirmed. Therefore, it is preferred to use a dispersion of a substance obtained by performing PVA addition reaction on PMMA in emulsification.
[0199] In Examples 1 to 6, even after 3 months at room temperature of 25° C. after emulsification, no phase separation was observed by physical appearance observation, and the emulsified state was confirmed to be maintained. Therefore, it was shown that the storage stability of the emulsified composition was also good.
[0200] [Table 6]
[0201] Table 6: Results of emulsification tests of Examples
[0202] composition Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Mineral oil 7 7 7 7 7 7 BG 1 1 1 1 1 1 Particles of Production Example 3 0.1 - - - - - Particles of Production Example 4 - 0.1 - - - - Particles of Production Example 5 - - 0.1 - - - Particles of Production Example 6 - - - 0.1 - - Particles of Production Example 8 - - - - 0.1 - Particles of Production Example 9 - - – - - 0.1 Elix Water The remainder The remainder The remainder The remainder The remainder The remainder total 10 10 10 10 10 10 Emulsion formation 〇 ○ 〇 〇 〇 ○ Emulsification type O / W O / W O / W O / W O / W O / W
[0203] (Unit: g)
[0204] [Table 7]
[0205] Table 7: Results of emulsification test of comparative example
[0206] composition Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Mineral oil 7 7 7 7 BG 1 1 1 1 PVA 0.1 – - - Particles of Production Example 1 - 0.1 - - Particles of Production Example 2 - - 0.1 - Particles of Production Example 7 - - - 0.1 Pure water The remainder The remainder The remainder The remainder total 10 10 10 10 Emulsion formation × × × × Emulsification type - - - -
[0207] (Unit: g)
[0208] <Experimental Example 2: Confirmation of Pickering Emulsion>
[0209] [Observation method of emulsion using fluorescent labeled particles]
[0210] Take about 10 μL of the emulsion composition prepared in Examples 1 to 4, place it on a film bottom dish (manufactured by ibidi), and dilute it with about 500 μL of water. Do not blow during dilution to avoid excessive destruction of the emulsion. Use a confocal laser microscope (trade name: FV1000, manufactured by Olympus) to observe fluorescence with a 100x oil immersion objective lens under the conditions of an excitation wavelength of 473 nm and a fluorescence wavelength of 485 nm to 585 nm. The microscope image is shown in Figure 2 The observation results showed that fluorescent particles were present at the interface between the oil phase and the water phase, indicating that a Pickering emulsion was formed.
[0211] <Example 3; Determination of interfacial tension value>
[0212] [Method for measuring interfacial tension value]
[0213] The interfacial tension was measured using the pendant drop method. As the surrounding phase, decamethylcyclopentasiloxane (cyclopentasiloxane, commonly known as "D5", with a specific gravity of 0.96 g / cm 3 , trade name: KF-995, manufactured by Shin-Etsu Chemical Co., Ltd.). Under the conditions of room temperature 25°C and humidity 44%±6%, a contact angle meter (trade name: DMo-502, manufactured by Kyowa Interface Science Co., Ltd.) was used. After the aqueous dispersion was sealed in a syringe, a hanging drop was discharged into the surrounding phase using an injection needle (needle size), and the shape of the hanging drop was analyzed using the Young-Laplace method (analysis software name: FAMAS7.2.0, manufactured by Kyowa Interface Science Co., Ltd.), thereby calculating the interfacial tension value (static interfacial tension value). In Preparation Examples 1 and 4, the measurement objects were set to aqueous dispersions with respective solid content masses of 1 mass%, 0.1 mass%, 0.01 mass%, 0.001 mass%, and 0.0001 mass%, and in Preparation Examples 5, 6, and 9, the measurement objects were set to aqueous dispersions with respective solid content masses of 1 mass%. The measurement operation was repeated 3 times.
[0214] [Results of interfacial tension measurement]
[0215] The results of the interfacial tension measurement are shown in Figure 3and Table 8. In Production Example 1, the dispersion concentration was in the range of 0.01% by mass to 1%, and the change in the interfacial tension value was 1 mN / m or less. In contrast, in Production Example 4, a decrease in the interfacial tension value of 20 mN / m or more was observed. It can be seen that the dispersion in Production Example 4 has an excellent effect of reducing the interfacial tension with D5 when the solid content is 0.01% by mass or more.
[0216] In addition, the measurement results of the aqueous dispersions with a solid content of 1% by mass in Production Example 1, Production Example 4, Production Example 5, Production Example 6, and Production Example 9 are shown in Table 8. The interfacial tension value of the dispersion in Production Example 1 was 28 mN / m. In contrast, the interfacial tension values of Production Example 4, Production Example 5, Production Example 6, and Production Example 9 were all 20 mN / m. That is, compared with Production Example 1, Production Example 4, Production Example 5, Production Example 6, and Production Example 9 showed smaller interfacial tension values, indicating an excellent effect of reducing the interfacial tension.
[0217] [Table 8]
[0218] Table 8: Results of interfacial tension value measurement
[0219]
[0220] <Example 4: Extraction test and FT-IR-based analysis of insoluble fraction after extraction>
[0221] [Method of extraction test]
[0222] In Production Example 1 and Production Example 4, after performing the washing and concentration operations described in <Washing and Concentration of PMMA-PVA Dispersion>, they were frozen at -80°C and then dried using a vacuum freeze-drying apparatus. The obtained dry powders were respectively put into a Soxhlet extractor together with 100 mL of chloroform as an extraction solvent at 1.23 g and 1.98 g, and extraction was carried out for 16 hours, and the mass of the extraction cylinder before and after extraction was measured.
[0223] Here, the reason for using chloroform as the extraction solvent is that PMMA is soluble in chloroform, but PVA is insoluble in chloroform. Specifically, for the chloroform required to dissolve 1 g of PMMA produced in Production Example 1, 10 mL is sufficient, but to dissolve 1 g of PVA, more than 10,000 mL of chloroform is required.
[0224] [Results of extraction test]
[0225] The results of the extraction test are shown in Table 9. In Production Example 1, the mass of the dry powder input was 1.23 g, the mass of the cylinder before extraction was 2.97 g, and the mass of the cylinder after extraction was 2.97 g. In Production Example 4, the mass of the dry powder input was 1.98 g, the mass of the cylinder before extraction was 2.90 g, and the mass of the cylinder after extraction was 3.08 g. In Production Example 4, the mass of the insoluble fraction after extraction (=(mass of the cylinder after extraction)-(mass of the cylinder before extraction)) was 0.18 g. In addition, the residual rate (%) of the insoluble fraction after extraction (=(mass of the insoluble fraction) / (mass of the dry powder input)×100) was 0% in Production Example 1 and 9.1% in Production Example 4. That is, in Production Example 1, no change in the mass of the extraction cylinder before and after extraction was observed, but in Production Example 4, the mass of the extraction cylinder after extraction was larger than that before extraction.
[0226] [Table 9]
[0227] Table 9: Results of extraction tests
[0228] Production Example 1 Production Example 4 Input dry powder mass [g] 1.23 1.98 Cylinder mass before extraction [g] 2.97 2.9 Cylinder mass after extraction [g] 2.97 3.08
[0229] The above results not only show that there is a difference in the structure of the portion corresponding to the hydrophobic part between Production Example 1 and Production Example 4, but also show that in Production Example 4, PVA is added to the portion corresponding to the hydrophobic part.
[0230] [Analysis method of insoluble fraction after extraction by FT-IR]
[0231] For the dispersions obtained in Preparation Examples 1 and 4, the insoluble fraction after the extraction test was taken out, and the residual extraction solvent was vacuum dried. The dried insoluble fraction after the extraction test, and the freeze-dried powders of PVA and PMMA were measured using Fourier transform infrared spectroscopy (FT-IR) (trade name: Nicolet 6700, manufactured by Thermo Fisher).
[0232] [Results of FT-IR analysis of the insoluble fraction after extraction]
[0233] The results of the analysis of the insoluble fraction after the extraction test by Fourier transform infrared spectroscopy (FT-IR) are shown in Figure 4 and Figure 5 (Trade name: Nicolet 6700, manufactured by Thermo Fisher). Figure 5 Yes Figure 4 The spectrum of is enlarged with a similar figure and the axis labels translated into Chinese. Figure 4 and Figure 5The three spectra show the FT-IR spectra of the insoluble fraction after the extraction test of Production Example 4, PVA, and the freeze-dried powder of Production Example 1 (PMMA). The spectrum of the insoluble fraction after the extraction test of Production Example 4 and the spectrum of PVA have a wavelength of 3200 cm -1 Up to 3500cm -1 The peak at 1700 cm (believed to be derived from alcohol OH stretching) -1 The peaks of (presumably derived from carboxylic acid C=O stretching) are consistent. In addition, the spectrum of the insoluble fraction after the extraction test of Production Example 4 is similar to that of PVA in terms of the overall characteristics of the spectrum. These results indicate that the insoluble fraction contains structures derived from PVA.
[0234] Furthermore, the insoluble fraction after the extraction test of Production Example 4, PVA, and the freeze-dried powder of Production Example 1 (PMMA) were measured using Fourier transform infrared spectroscopy (FT-IR) (trade name: Nicoleti S50, manufactured by Thermo Fisher).
[0235] [Results 2 of FT-IR analysis of the insoluble fraction after extraction]
[0236] The results of the analysis of the insoluble fraction after the extraction test by Fourier transform infrared spectroscopy (FT-IR) are shown in Figure 6 (Trade name: Nicoleti S50, manufactured by Thermo Fisher). Figure 6 The four spectra are numbered from A to D from top to bottom. Spectrum A represents the insoluble fraction after the extraction test of Production Example 4, spectrum B represents PVA, spectrum C represents the freeze-dried powder of Production Example 1 (PMMA), and spectrum D represents the difference spectrum between A and B. -1 Up to 3500cm -1 The peak at 1700 cm (believed to be derived from alcohol OH stretching) -1 The peaks (believed to be derived from the C=O stretching of carboxylic acid) are consistent. In addition, in terms of the overall characteristics of the spectra, spectra A and B are also similar. If a library search of FT-IR spectra is performed on spectrum A (program name: OMNIC9.13, manufactured by ThermoFisher), PVA with a saponification degree of 88 mol% is hit with a maximum hit rate of 76%. In addition, the overall characteristics of spectra C and D are very similar. If a library search of FT-IR spectra is performed on spectrum D, PMMA is hit with a maximum hit rate of 85%. According to these results, the insoluble fraction contains structures derived from PVA and PMMA.
[0237] <Comparative Example 1: Preparation of PMMA-PVA Dispersion Using Anionic Radical Polymerization Initiator>
[0238] [Manufacturing Example 10 and Manufacturing Example 11: Preparation of PMMA-PVA Dispersion Using Anionic Radical Polymerization Initiator]
[0239] First, 3 g of methyl methacrylate (MMA) and Elix water replaced with argon were added to a 30 mL transparent glass vial (trade name: SV-30, manufactured by Nichiden Rika Glass Co., Ltd.) in the formulation shown in Table 1 above so that the total volume became 30 mL. 41 mg of potassium persulfate (anionic radical polymerization initiator) and 1.7 μL of N,N,N',N'-tetramethylethylenediamine were added thereto, and stirred for 4 hours in a hot water bath at 80° C. using a strong stirrer, thereby obtaining a PMMA dispersion polymerized using anionic radical polymerization initiator.
[0240] Next, the PMMA dispersion polymerized using an anionic free radical polymerization initiator was added to a 300 mL separable flask with a baffle in such a way that the final solid content mass became 4.8 g, 2.7 g of the specified polyvinyl alcohol recorded in Table 10 was added thereto, and Elix water was added in such a way that the total mass became 199 g. Then, the solution was heated to 60°C while stirring at a stirring speed of 450 rpm. Furthermore, 27 mg of potassium persulfate and 1 μL of N,N,N',N'-tetramethylethylenediamine were added, and stirred at a stirring speed of 450 rpm for 3 hours under the temperature conditions described in Table 10. Finally, the washing and concentration operations were performed in the same manner as the above [washing and concentration operations] to obtain a PMMA-PVA dispersion polymerized using an anionic free radical polymerization initiator.
[0241] [Table 10]
[0242] Table 10: Details of the particles produced and interfacial tension values
[0243]
[0244] <Comparative Example 2: DLS Measurement of PMMA-PVA Dispersion Using Anionic Radical Polymerization Initiator and Measurement of Interfacial Tension Value>
[0245] For Manufacturing Examples 10 and 11, DLS measurement and interfacial tension measurement between the 1% mass dispersion and D5 were performed, and the results are shown in Table 10. Both Manufacturing Examples 10 and 11 are dispersions with negative zeta potential, which are anionic dispersions. In addition, the interfacial tension value is 25.7 mN / m, indicating that it is not easy to cause interfacial tension reduction compared with Manufacturing Examples 4, 5, 6 and 9.
[0246] <Comparative Example 3: Preparation of an Emulsified Composition of PMMA-PVA Dispersion Using an Anionic Radical Polymerization Initiator>
[0247] In the method described in <Experimental Example 1; Preparation of Emulsified Composition>, the PMMA dispersion or PMMA-PVA dispersion was replaced with the dispersion prepared in Manufacturing Example 10 or Manufacturing Example 11, and the preparation operation of the emulsified composition was performed, and the appearance of the properties was observed 1 minute after the stirring was completed. As a result, phase separation was observed, and it was confirmed that a uniformly emulsified emulsified composition was not obtained. Therefore, it is shown that the particles of the present invention need to have at least a cationic group.
[0248] <Manufacturing Example 12 and Manufacturing Example 13: Synthesis of PMMA-PVA Particle Dispersion>
[0249] 42g of MMA and 166g of Elix water were added to a 300mL separable flask with baffles. Using a sealed mixer UZU, the temperature was raised to 80°C while stirring at 450rpm, and then 0.22g of 2,2'-azobis(2-methylpropionamidine) dihydrochloride (V-50, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was dissolved in 2g of pure water and the whole amount was added and synthesized for 6 hours (Manufacture Example 12). The solid content of the obtained emulsion was 19.5% by mass.
[0250] Preparation Example 12 differs from Preparation Examples 1 and 2 in terms of the synthesis container, stirring, time and temperature conditions. In addition, methanol was not used as a solvent. In addition, the conditions for making the mass ratio of the MMA monomer in the total mass high and the use of V-50 as a cationic polymerization initiator are different.
[0251] Next, the PMMA dispersion prepared in Manufacturing Example 12 was added to a 300 mL separable flask with a baffle in such a way that the final solid content mass became 30 g, 15 g of PVA (trade name: EG-05C, manufactured by Mitsubishi Chemical Corporation) and 0.07 g of sodium acetate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were added thereto, and Elix water was added in such a way that the total mass became 198 g. Then, the solution was heated to 80°C while stirring at a stirring speed of 450 rpm, and stirring was continued for 1 hour to dissolve the polyvinyl alcohol. After 1 hour from the heating, the substance obtained by dissolving 0.19 g of ADIP-Cl in 2 g of pure water was put into the solution adjusted to 60°C in all amounts, and synthesized for 3 hours (Manufacturing Example 13).
[0252] Production Example 13 has a higher mass ratio of the PMMA dispersion and PVA in the total mass than Production Examples 3 and 4. In addition, the addition of sodium acetate is different.
[0253] The results are shown in Table 11. Preparation Examples 12 and 13 are monodispersed cationic particles. In addition, the interfacial tension value of the sample after the washing operation of Preparation Example 13 is smaller than that of Preparation Example 1, and the effect of reducing the interfacial tension is excellent. Preparation Examples 12 and 13 have good storage stability.
[0254] [Table 11]
[0255] Table 11: Details of the samples produced
[0256]
[0257] <Manufacturing Examples 14 to 19: Synthesis of dispersions of copolymers of MMA and styrene (MMA-St copolymers) or copolymers of MMA and butyl acrylate (MMA-BA copolymers)>
[0258] As shown in Table 12, the reagents were added to a 30 mL transparent glass vial (trade name: SV-30, manufactured by Nichiden Rika Glass Co., Ltd.) so that the total content was 30 g, and synthesis was performed at 60° C. for 16 hours using a strong stirrer. Under all synthesis conditions, no obvious coarse aggregates were confirmed in the obtained dispersion.
[0259] [Table 12]
[0260] Table 12: Synthesis conditions of Preparation Examples 14 to 19
[0261]
[0262] These conditions differed from those in Production Examples 1 and 2 in that MMA and styrene (St) or MMA and butyl acrylate (BA) were added as monomers. In addition, methanol was not used as a solvent.
[0263] <Production Examples 20 to 25: PVA Modification Step of MMA-St Copolymer or MMA-BA Copolymer>
[0264] As shown in Table 13, the reagents were added to a 300 mL separable flask with a baffle in such a manner that the total content became 200 g. Particles of MMA-St copolymer (Manufacturing Example 14 or Manufacturing Example 15) or MMA-BA copolymer (Manufacturing Example 16 to Manufacturing Example 19) were added in such a manner that they became 4.8 g, and PVA was added in a powder state and stirred at 60°C for 1 hour to dissolve it. Then, an initiator was added and the sealed mixer UZU was used to synthesize for 3 hours at 450 rpm and 60°C. The solid content and PVA addition rate of the synthesized emulsion were measured. Furthermore, the obtained emulsion was centrifuged at 8000 rpm for 30 minutes using a large centrifuge. The supernatant was removed, pure water was added, and the solid content was redispersed, thereby washing was performed. Repeat the washing twice. After the washing was completed, centrifuged again at 8000 rpm for 30 minutes, the supernatant was removed, and then pure water was added in such a manner that the final concentration of the solid content mass became 10wt%, and redispersed.
[0265] [Table 13]
[0266] Table 13: Preparation conditions of P (MMA-St copolymer or MMA-BA copolymer)-PVA
[0267]
[0268] <Details of the created particles>
[0269] The average particle size, the degree of dispersion (PdI), the average zeta potential, the solid content mass concentration, and the PVA addition ratio were measured by the same method as described in the above-mentioned <Analysis Method>.
[0270] ( 1 H-NMR measurement and calculation of copolymerization ratio of MMA)
[0271] Using proton nuclear magnetic resonance ( 1 H-NMR) was used to calculate the copolymer composition ratio (MMA unit, mol%) of the particles of Manufacturing Examples 14 to 19. The measurement was performed using AV-300N (manufactured by Bruker). Weigh 2 mg of the dry-heat dried sample, dissolve it in 1 mL of deuterated chloroform (tetramethylsilane 0.05 wt%, manufactured by Tokyo Chemical Industry Co., Ltd.) for one night, and seal the obtained substance in an NMR tube for measurement (300 MHz, cumulative number of 16 times). The measurement benchmark was set to CHCl3 (7.26 ppm) and tetramethylsilane (0.00 ppm). Based on the signal intensity of the structures derived from MMA, styrene, and butyl acrylate in the obtained spectrum, the MMA unit relative to the overall copolymer composition was calculated.
[0272] (Glass transition temperature measurement based on differential scanning calorimetry)
[0273] Regarding Production Examples 14 to 19, the glass transition temperature of the freeze-dried powder after the washing operation was measured by differential scanning calorimetry (DSC) (measurement conditions: heating rate: 20°C / min, measurement temperature range: -50°C to 100°C, nitrogen flow: 50 mL / min, reference: empty pan (aluminum crimp), measurement apparatus: EXSTAR DSC7020 (manufactured by Hitachi High-Tech Science Corporation)), and the more specific DSC measurement method was in accordance with the method described in JIS K 7121 (1987).
[0274] The measurement results are shown in Table 14 below.
[0275] [Table 14]
[0276] Table 14: Details of the particles produced
[0277]
[0278] <Preparation of Emulsified Composition>
[0279] In the manner that the solid content mass becomes 1 mass %, manufacturing examples 4 and manufacturing examples 20 to 25 are added to a 300 mL disposable cup, respectively, 10 g of BG and the mass of Elix water recorded in Table 15 are weighed, and a homogenizer (trade name: small desktop machine Laboration (R) for ultra-high-speed emulsification and dispersion device research, stirring part: MARKII2.5 type, PRIMIX Corporation system) is used to stir at 2000 rpm. Then 140 g of decamethylcyclopentasiloxane (trade name: KF-995, Shin-Etsu Chemical Co., Ltd.) is slowly added. After the addition is completed, stir at 2000 rpm for 1 minute, and then stir at 4500 rpm for 3 minutes to prepare an emulsion. By observing the appearance of the properties 1 minute after the stirring is completed, no phase separation is found, and it is confirmed that it has been emulsified.
[0280] The above results are shown in Table 15. In all of Examples 7 to 13, emulsification was confirmed, and the emulsification type was O / W.
[0281] [Table 15]
[0282] Table 15: Results of emulsification tests of Examples
[0283] composition Example 7 Example 8 Example 9 Example 10 Embodiment 11 Example 12 Embodiment 13 Decamethylcyclopentasiloxane 140 140 140 140 140 140 140 BG 10 10 10 10 10 10 10 Particles of Production Example 4 2 Particles of Production Example 20 - 2 - - - - - Particles of Production Example 21 - - 2 - - - - Particles of Production Example 22 - - 2 - - - Particles of Production Example 23 - - - - 2 - - Particles of Production Example 24 - - - - - 2 - Particles of Production Example 25 - - - - - - 2 Elix Water The remainder The remainder The remainder The remainder The remainder The remainder The remainder total 200 200 200 200 200 200 200 Emulsion formation 〇 〇 〇 ○ 〇 ○ 〇 Emulsification type O / W O / W O / W O / W O / W O / W O / W
[0284] (Unit: g)
[0285] <Molecular weight determination by gel permeation chromatography>
[0286] Gel permeation chromatography (GPC) analysis was performed on PVA (trade name: JP-05, manufactured by JAPAN VAM & POVAL CO., LTD., saponification degree: 88 mol%, average polymerization degree: 500), Preparation Example 1, Preparation Example 4, and the dried product of the insoluble fraction after extraction of Preparation Example 4 (the insoluble fraction after extraction of Preparation Example 4 after the extraction test in Example 4 was performed).
[0287] PVA, the freeze-dried products of Preparation Examples 1 and 4, and the dried product of the insoluble fraction after extraction of Preparation Example 4 were dissolved in hexafluoroisopropanol (10 mmol / L sodium trifluoroacetate solution) to 0.2 w / v%. As a pretreatment, it was treated with a 0.2 μm PTFE membrane filter. As for the measuring device, GPC-104 (manufactured by Shoko Science Co., Ltd.) was used as the RI detector. As for the column, a column obtained by connecting two Shodex GPC LF-404 (manufactured by Showa Denko K.K.) was used. The column temperature was set to 40°C, the flow rate was set to 0.3 mL / min, and the injection volume was set to 10 μL. As a standard substance, polymethyl methacrylate (PMMA) was used to prepare a standard curve and calculate the molecular weight of each sample.
[0288] The results are shown in Table 16. The GPC analysis results of Production Examples 1 and 4 showed that the number average molecular weights were 150,000 and 130,000, respectively, and the weight average molecular weights were 580,000 and 560,000, respectively. In addition, the GPC analysis results of the insoluble fraction after extraction and PVA in Production Example 4 showed that the number average molecular weights were 75,000 and 39,000, respectively, and the weight average molecular weights were 150,000 and 82,000, respectively.
[0289] [Table 16]
[0290] Table 16: Molecular weight determination based on gel permeation chromatography
[0291]
[0292] By this result, the dried product (PMMA-PVA dispersion) of the insoluble fraction after extraction of manufacturing example 4 is compared with PVA, and the number average molecular weight and weight average molecular weight of the dried product of the insoluble fraction after extraction of manufacturing example 4 are greater. In the extraction test of embodiment 4, PMMA is dissolved in chloroform used as a solvent, and PVA is insoluble in chloroform used as a solvent, so in the PMMA-PVA dispersion, PMMA is extracted, and PMMA is not contained in the dried product of the insoluble fraction after extraction. On the other hand, as mentioned above, differences are observed in number average molecular weight and weight average molecular weight, so in manufacturing example 4, it is observed that the molecular weight increases due to the combination of PVA and PMMA, etc.
[0293] <Production of Formulation Composition Containing Ultraviolet Absorbent>
[0294] (Reference Example 1)
[0295] 2 - ethylhexyl 2 - cyano - 3,3 - diphenylacrylate (hereinafter referred to as octocrylene, manufactured by Tokyo Chemical Industry Co., Ltd.) and pentaerythritol tetra(2 - ethylhexanoate) (manufactured by Fujifilm Wako Pure Chemical Corporation), which are ultraviolet absorbers described in Table 17, were mixed to obtain an oily composition.
[0296] (Reference Examples 2 to 4)
[0297] Components other than octocrylene and pentaerythritol tetra(2 - ethylhexanoate) (manufactured by Fujifilm Wako Pure Chemical Corporation), which are ultraviolet absorbers described in Table 17, were added and stirred with a homogenizer at 2000 rpm. Then, the oily composition (Reference Example 1) was slowly added. After the addition was completed, it was stirred at 2000 rpm for 1 minute and then at 4500 rpm for 3 minutes to obtain an emulsified composition. Regarding Reference Examples 2 to 4, no phase separation or the like was observed by observing the appearance of the property 1 minute after the stirring was completed, and thus it was confirmed that emulsification had occurred.
[0298] [Table 17]
[0299] Table 17: Formulation Conditions Containing Ultraviolet Absorbent and Results of Emulsification Tests
[0300] Reference Example 1 Reference Example 2 Reference Example 3 Reference Example 4 Batch number 230323-1 230323-2 230323-3 230323-4 composition Octocrylene 10 10 10 10 Pentaerythritol tetra(2-ethylhexanoate) 130 130 130 130 BG 0 20 20 20 PVA 0 0 4 2 Particles of Production Example 4 0 0 0 2 Twain 80 0 4 0 0 Elix Water 0 36 36 36 total 140 200 200 200 Emulsion formation - ○ ○ 〇 Emulsification type - O / W O / W O / W
[0301] (Unit: g)
[0302] That is, in Reference Examples 2 to 4, the oil phase containing organic compounds such as ultraviolet absorbers was emulsified in an O / W emulsion type.
[0303] <Measurement of Thickness of PVA Layer>
[0304] Manufacturing Examples 1, 4, and 5 were washed and concentrated using the above [Washing and Concentration Operations], and then adjusted with pure water so that the solid content mass became 0.001 mass%. The thickness of the PVA layer was measured using a particle size, Zeta potential, and molecular weight measurement device (trade name: Zetasizer Nano ZSP, manufactured by Malvern Panalytical), and the analysis software used was Zetasizer Software 7.12 manufactured by Malvern. The average particle size was the average of three measurements.
[0305] The thickness of the PVA layer was calculated using the following formula with reference to non-patent literature (Colloids and Surfaces A: Physicochemical and Engineering Aspects, August 2014, 456, 139-145) and non-patent literature (Journal of Colloid and Interface Science, March 2020, 562, 204-212).
[0306] [Mathematical formula 3]
[0307] Thickness of PVA layer = 0.5 × {(average particle size of PMMA-PVA dispersion) - (average particle size of PMMA dispersion)}
[0308] The results are shown in Table 18. The thickness of the PVA layer was calculated to be 15 and 16 nm in Production Examples 4 and 5, respectively. The average particle size of the PMMA-PVA dispersion was larger than that of the PMMA dispersion, and it was confirmed that a PVA layer was formed on the surface of the PMMA particles, indicating that PVA was still added to the surface of the PMMA particles after the washing operation.
[0309] [Table 18]
[0310] Table 18: Measurement results of the thickness of the PVA adsorption layer
[0311]
Claims
1. A particle comprising: a hydrophobic portion comprising a hydrophobic monomer unit and having a cationic group; and a hydrophilic portion comprising at least a hydrophilic monomer unit represented by the following formula (I), [Chemical formula 1] 。 2. The particle according to claim 1, wherein A part or the whole of the surface of the hydrophobic part is directly or indirectly covered with the hydrophilic monomer or the polymer thereof.
3. The particle according to claim 1 or 2, wherein The cationic group is derived from a cationic radical polymerization initiator.
4. The particle according to claim 1 or 2, wherein The hydrophobic monomer unit is a monomer unit having an ethylenically unsaturated double bond.
5. The particle according to claim 4, wherein The monomer unit having an ethylenically unsaturated double bond is a (meth)acrylic monomer unit.
6. The particle according to claim 4, wherein The monomer unit having an ethylenically unsaturated double bond is a styrene-based monomer unit.
7. The particle according to claim 3, wherein The cationic radical polymerization initiator is selected from 2,2'-[diazen-1,2-diylbis(propane-2,2-diyl)]bis(1,3-dimethyl-4,5-dihydro-1H-imidazol-3-ium)=bis(trifluoromethanesulfonate) salt (ADIP), 2,2'-[diazen-1,2-diylbis(propane-2,2-diyl)]bis(1,3-dimethyl-4,5-dihydro-1H-imidazol-3-ium)=bis(trifluoromethanesulfonate) salt (ADIP), At least one of the group consisting of 2,2'-azobis(2-methylpropionamidine) dihydrochloride (V-50), 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride (VA-044), and 2,2'-azobis[2-(2-imidazolin-2-yl)propane] (VA-061).
8. The particle according to claim 1 or 2, wherein The hydrophilic portion further comprises a monomer unit represented by the following formula (II), wherein the ratio (degree of saponification) of the number of the monomer units represented by the formula (I) to the total number of the monomer units represented by the formula (I) and the number of the monomer units represented by the following formula (II) is 70% or more and 99% or less, [Chemical formula 2] 。 9. The particle according to claim 8, wherein The ratio (degree of saponification) of the number of the monomer units represented by the formula (I) to the total number of the monomer units represented by the formula (I) and the monomer units represented by the formula (II) is 78% or more and 90% or less.
10. The particle according to claim 1 or 2, wherein The mass corresponding to the hydrophilic part is equal to 1 part by mass or more and 6 parts by mass or less with respect to 100 parts by mass corresponding to the hydrophobic part. The particle according to claim 1 or 2, wherein the average zeta potential is not less than +10 mV and not more than +60 mV. 12 . The particle according to claim 1 , wherein the cumulative average diameter is from 100 nm to 500 nm.
13. The particle according to claim 2, wherein The hydrophobic monomer unit and the hydrophilic monomer unit are bonded to each other through a covalent bond, and a part or the whole of the surface of the hydrophobic part is directly covered with the hydrophilic monomer or a polymer thereof.
14. The particle according to claim 2, wherein The hydrophobic monomer unit and the hydrophilic monomer unit are bonded to each other by intermolecular force, and a part or the whole of the surface of the hydrophobic part is indirectly covered with the hydrophilic monomer or a polymer thereof.
15. The particle according to claim 14, wherein The above-mentioned bonding based on intermolecular forces is brought about by heating treatment.
16. The particle according to claim 1 or 2, wherein The interfacial tension value (T 0.01 ), and the difference (T1) between the interfacial tension value (T2) between the aqueous dispersion containing 1% by mass of the particles and decamethylcyclopentasiloxane. 0.01 -T1) is 10mN / m or more.
17. The particle according to claim 1 or 2, wherein Interfacial tension value (T 0.01 ) is less than 25mN / m.
18. The particle according to claim 1 or 2, wherein The relative ratio of the molecular weight of only the hydrophobic part to the molecular weight of only the hydrophilic part per unit particle is 1 to 6 for the hydrophilic part relative to 100 for the hydrophobic part.
19. The particle according to claim 1 or 2, wherein The residual rate of the insoluble fraction after extraction with a Soxhlet extractor using chloroform as an extraction solvent was 5% or more.
20. The particle of claim 1 or 2, for use in forming a Pickering emulsion.
21. The method for producing the particles according to claim 1 or 2, comprising: A step of polymerizing a hydrophobic monomer in the presence of a cationic free radical polymerization initiator and an emulsifier; A step of polymerizing a hydrophilic monomer separately from the hydrophobic monomer or after the polymerization of the hydrophobic monomer is completed; and A step of combining or associating the polymerized hydrophobic monomer with the polymerized hydrophilic monomer.
22. The particle according to claim 1 or 2, comprising a polymer having a hydrophobic portion and a hydrophilic portion.
23. The particle of claim 22, wherein The number average molecular weight of the polymer having a hydrophobic part and a hydrophilic part is 1,000 or more and 500,000 or less.
24. The particle of claim 22, wherein The glass transition temperature of the polymer having a hydrophobic portion and a hydrophilic portion is 30° C. or higher and 200° C. or lower.
25. The particle of claim 1 or 2, wherein The hydrophobic monomer is at least one selected from the group consisting of methyl methacrylate, styrene, and butyl acrylate.
26. The particle of claim 20, wherein The Pickering emulsion is an emulsion suitable for use on the skin.
27. The particle of claim 20, wherein The Pickering emulsion comprises an aromatic compound.
28. The particle of claim 27, wherein The aromatic compound is an ultraviolet absorber or a preservative.
29. The particle of claim 20, wherein The Pickering emulsion is a Pickering emulsion that does not allow the aromatic compound contained in the Pickering emulsion to penetrate into the inside of the skin.
30. The particle of claim 13, wherein The hydrophobic monomer unit and the hydrophilic monomer unit are bonded by a covalent bond, and a part or the entirety of the surface of the hydrophobic portion is directly covered with a polymer of the hydrophilic monomer, and the thickness of the layer of the polymer of the hydrophilic monomer is 0.001 nm to 200 nm.
Citation Information
Patent Citations
Cement composition
JP2009102216A
Intracellular delivery vehicle
JP2017051113A
Pickering emulsion containing acrylic polymer
JP2019202962A
Program, information processing method, and information processing apparatus
JP2022095286A